Efficient anonymous roaming authentication scheme using certificateless aggregate signature in wireless network - Dan LIU; Run-hua SHI; Shun ZHANG; Hong ZHONG (Tongxin xuebao)
To solve the privacy-preserving problem during the roaming authentication of wireless mobile networks, a novel roaming authentication scheme with anonymity was presented. An efficient certificateless aggregate signature scheme was first constructed, by introducing the online/offline signature and combining the aggregate signature. Com-pared with the related schemes, the proposed scheme has higher efficiency in computations of both signature and verifi-cation, and also improves the efficiency in communications. Furthermore, based on the proposed signature scheme, a novel roaming authentication scheme with anonymity was presented, in which it simplified the traditional three-party au-thentication model. The theoretical analysis shows that this scheme is secure and effective, and thus it is especially suit-able for large-scale wireless mobile networks.